A Comparative Study to Evaluate the Effect of Jalaukavacharana and Shalmali Kantaka Lepa in the Management of Mukhadushika w.s.r. to Acne Vulgaris - Shivaji Bhadauria; Charu Supriya (AYUSHDHARA, 2025)
Mukhadushika (acne vulgaris) is a common skin condition in adolescents, caused by inflammation, excess sebum and bacterial growth. In Ayurveda, Mukhadushika is linked to imbalances in Vata, Kapha and Rakta doshas. It can cause significant psychological distress, affecting self-esteem and social interactions. While modern treatments focus on topical and systemic medications, Ayurvedic therapies like Jalaukavacharana (leech therapy) and Shalmali Kantaka Lepa offer alternative approaches for managing the condition. Objective: A comparative study to evaluate the effect of Jalaukavacharana and Shalmali Kantaka Lepa in the management of Mukhadushika w.s.r. Acne Vulgaris. Methodology: A randomized clinical trial was conducted at RGGPG Ayurvedic College, Paprola, with 40 Mukhadushika (acne) patients divided into two groups. Group A received Jalaukavacharana with Shalmali Kantak Lepa, while Group B treated with Lepa. Result: The study showed that the results in the Jalaukavacharana along with Lepa group were significantly better than in the Lepa-only group, highlighting the beneficial synergistic effects of combining Jalaukavacharana with Shalmali Kantak Lepa alone. Conclusion: The study shows that combining Jalaukavacharana with Shalmali Kantak Lepa offers superior therapeutic benefits for treating chronic Mukhadushika. This integrative approach enhances treatment efficacy, providing a promising alternative to conventional acne management.